Boosting firm dynamism and performance in China - Molnar, Margit (OECD Economics Department Working Papers, 2017)
With persisting slower growth worldwide and in China, over-capacity in some heavy industry sectors, declining profitability, and intensifying competition from other, lower-cost emerging economies, corporate behaviour in China needs to change and focus more on efficiency and sustainability. This need is further intensified by mounting environmental pressures and China's ambition for greener and more sustainable growth. A larger proportion of firms, including state-owned enterprises, should step up innovation efforts and improve corporate governance practices. To this end, supportive policies are needed, fostering an environment that is more conducive to innovation and entrepreneurship, and facilitating resource reallocation through the exit of unviable firms. At the same time, fraudulent corporate practices must be halted and State assets need to be better managed. Reforms are under way or envisaged that will help improve corporate performance and, more broadly, deliver more resilient and environmentally sustainable growth and continuing progress in living standards. This Working Paper relates to the 2017 OECD Economic Survey of China (www.oecd.org/eco/surveys/economic-survey-china.htm)